Co-generation of NaREE(MoO4)2 and REEPO4 in multiple habits by solid-flux crystal growth - Joseph Brian Balta; Megan E. Holycross; Buz Barstow; Esteban Gazel (PLoS ONE, 2025)
Rare Earth Elements (REE) are key to modern technology and industrial processes. They are most used in electronics, although their chemistry enables numerous other applications. Oxides that combine REE, sodium, and molybdenum can be used as catalysts, antibacterial agents, pigments, and even as components in lasers. Although they are heavily in demand, REE supplies are limited in part because the separation of REE from monazite and xenotime (REEPO 4 ), some of the most abundant REE bearing minerals in natural rocks, requires high energy inputs and creates significant environmental hazards. Through an experimental study, here we demonstrate a rapid reaction between REE phosphates and a flux containing molybdenum oxide and sodium carbonate that converts mm-sized REE phosphate into NaREE(MoO 4 ) 2 in a period of hours at temperatures <870 °C. This reaction occurs using both lab-grown REEPO 4 and naturally occurring monazite as starting materials. The presence of crystalline REEPO 4 at higher temperatures (e.g., > 870 °C) limits the grain size of the coexisting oxide. The substantial reactive surface area of the small-grained oxides is advantageous for industrial catalysis processes or for usage as an antibacterial agent. Larger, mm-scale crystalline NaREE(MoO 4 ) 2 is produced if mm-scale REEPO 4 is not stable in the reaction products at high temperature. Finally, we offer updated details for procedures to grow mm-scale crystals of REEPO 4 using the same flux-growth technique, improving the ability to grow those crystals for industrial efforts or for creation of analytical standards.